Climatology of multiple‐stroke lightning in Japan. (14th February 2020) - Iwasaki, Hiroyuki
Abstract: In this work, the climatology of multiple‐stroke lightning (MSL) in Japan was studied using the World Wide Lightning Location Network's lightning data over a 9‐year period. The MSL ratio defined in this study for all types of lightning was 14.1%, and it was larger over the ocean than that over the continent. The mean multiplicity was 2.58 and was also larger over the ocean than that over the continent. The mean interstroke interval between the first and second strokes was longer for a height at which the temperature was −20°C, corresponding to the upper boundary of the higher negative charge area. Abstract : The climatology of multiple‐stroke lightning (MSL) in Japan was studied using the World Wide Lightning Location Network lightning data. The mean interstroke interval o MSL between the first and second strokes was longer for a height of −20°C level (H‐20), corresponding to the upper boundary of the higher negative charge area. Further, the basic parameters of MSL are largely variant according to regions.